Spatial Analysis of Food Security Index and Its Factor to Support Program Priority Area in Central Java, Indonesia - Syafinda Fyndiani, Saskia; Putri Titisari, Hanung; Fadhiil Al-Ghifaary, Muhammad; Handayani, Tiara; Fadhilah, Achmad (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Food security Index (FSI) is a global issue influenced by ecological and socio-economic factors. Food security is a condition in which humans can meet their food needs. Therefore, it is necessary to identify the conditions of food security and the factors that can influence it as a first step in overcoming food insecurity. The study area of this research is Central Java. This study uses spatial autocorrelation method. This method can determine patterns or correlations between study locations using Moran’s I and LISA. This method also provides information related to the relationship between poverty distribution characteristics between locations in Central Java. This study also analyzes the Food Security Index (FSI) in Central Java Province by integrating drought parameters (Normalized Difference Drought Index), poverty levels, food expenditure, and open unemployment rates. The results of the analysis show a correlation between ecological conditions and FSI achievements. These results confirm that the FSI level in the study area does not only depend on natural resources but is also influenced by socioeconomic factors. Thus, the results of this analysis may be beneficial as recommendations for policymakers through a spatial-based approach to provide strategies for improving food security, especially in Central Java.